Crimes in archival form: human rights, fact production, and Myanmar - MacLean, Ken (University of California Press, 2022)
Pacifying bodies : histories of preemptive violence -- Enslaving bodies : verbatim in replicated form -- Starving bodies : visual economies of enumeration -- Killing bodies : narrativity transcribed -- Investigating bodies : the recursive logic of citations.